2019
DOI: 10.2174/1874434601913010156
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Stages of Family Violence and their Perceived Solutions in Persons with Schizophrenia

Abstract: Background: Family violence committed by persons with schizophrenia is a serious problem in the context of the accelerated deinstitutionalization in Japan. Community nurses could play an important role in resolving family violence by persons with schizophrenia. Objective: This study aimed to clarify the reasons for family violence as perceived by adult children with schizophrenia and ways to resolve this problem. Methods: A q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 22 publications
(9 reference statements)
0
30
0
Order By: Relevance
“…Violence was assessed over different time intervals comprising: participants' lifetime 32,38,39,82,83 ; since patient illness onset 29,81 ; and 12 months preceding the study 30,31 . Three studies did not comment on time frame 35,36,44 . Four themes were identified: (i) the nature of violence; (ii) physical impacts; (iii) psychological/emotional impacts; and (iv) impacts on familial relationships (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Violence was assessed over different time intervals comprising: participants' lifetime 32,38,39,82,83 ; since patient illness onset 29,81 ; and 12 months preceding the study 30,31 . Three studies did not comment on time frame 35,36,44 . Four themes were identified: (i) the nature of violence; (ii) physical impacts; (iii) psychological/emotional impacts; and (iv) impacts on familial relationships (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Relatives shared challenges in understanding how to prevent or control violent episodes, conveying a sense of powerlessness. Uncontrollability was also echoed in patients' narratives 30,44 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most extant studies on this topic—all of which have utilized convenience sampling—have found approximately 20% of caregivers and other family members with high levels of contact with persons with SMI to have experienced violence by their relative with SMI in the past year (for a review see Labrum & Solomon, 2017 ). Family violence by persons with SMI has a range of noxious consequences for family members—such as psychological distress, trauma symptoms, and possible injury and death (Ahn et al, 2012 ; Onwumere et al, 2018 )—and for persons with SMI, including involvement in the criminal justice system and deteriorated relationship quality and disconnection from family members (Kageyama et al, 2018 , 2019 ; Labrum & Solomon, 2022 ; Onwumere et al, 2019 ).…”
mentioning
confidence: 99%